Movements and Dive Behaviour of Belugas in Northern Quebec - Kingsley, Michael C.S.; Gosselin, Serge; Sleno, Gary A. (ARCTIC, 2001)
Three adult and three juvenile belugas were fitted with satellite-linked radio tags in eastern Hudson Bay in mid-August 1993, and one adult was tagged in mid-October 1995 in extreme northeastern Hudson Bay. The tags transmitted data on dive behaviour, and the receiving satellite calculated positions by Doppler-shift triangulation. The belugas tagged in summer in eastern Hudson Bay made no directed or long-distance movements while the tags were attached. Their range did not include the Belcher Islands, and belugas observed in aerial surveys of those islands do not appear to belong to the eastern coastal stock. The single beluga tagged in northern Quebec in October moved into the deep water of western Hudson Strait and travelled east along the southern coast of Hudson Strait, slowing up on reaching shallower water off Salluit and near Charles Island. This whale was still off Salluit when the tag stopped transmitting. All the tagged belugas dived intensively while the tags were attached, although there were individual differences, some belugas diving noticeably less than others. Dive behaviour varied over time, with periods lasting several days of concentrated diving interspersed with periods of less intense diving. 'Intense' periods entailed diving for up to 80% of the time. All belugas, even the one that was in deep water in Hudson Strait, showed dive depth characteristics that were consistent with diving usually to the bottom. However, all belugas always - even in deep water - made dives that usually lasted less than 10 min and very seldom lasted more than 12 min. Belugas tagged as pairs of adults and young showed striking correlations of dive behaviour. The data obtained indicate that it would be appropriate to correct aerial surveys by adding 85% to aerial counts. Mi-août 1993, on a équipé trois bélougas adultes et trois bélougas juvéniles de radio-émetteurs en liaison avec un satellite dans l'est de la baie d'Hudson et mi-octobre 1995 on a équipé un adulte aux confins nord-est de la baie d'Hudson. Les ...